The hepatitis В virus: general description, physical structure, genetic organization, gene transcripts and genomic regulatory elements - Adjamian, F. (Биополимеры и клетка, 1999)
The HBV genome is a circular partially double-stranded DNA molecule. It contains four overlapping open reading frames (ORFs) genes. The S (preS1, preS2) region(s) encodes the major (small), middle and large proteins (HBsAg). The C and pre-C regions encode HBcAg and HBeAg. The X region encodes a polypeptide expressed during HBV infection. The P region codes for a protein with several, functions in replication. Four classes of HBV mRNAs have been identified, in the HBV genome the pre-S1 promoter expresses the large protein. The pre-S2/S promoters produce both major and middle proteins. The X promoter produces 0.7 and 0.9 kb transcripts. The C and pre-C promoters produce the Core, pol(HBcAg), and the HBeAg proteins. Enhancer I and II are key regulatory elements in the transcriptional regulation of HBV. The activity of enhancer II is highly the liwr specific. Enhancer II activates the transcriptional activity of both the pre-S1 and preS2/S promoters. Two HBV enhancers strongly affect the activity of all three major HBV promoters. A box-α in the II-A and box-β in II-B elements of HBV genome, are necessary for the enhancer II function. Either box-α or box-β can regulate the activity of the Core promoter, a, b, f proteins and c, d proteins bind to box-α and box-β, respectively, and mediate the enhancer function. Геном вірусу гепатиту В людини (HBV) існує у вигляді дволанцюгових кільцевих молекул ДНК Він містить чотири фланкуючі відкриті рамки зчитування (ORFs) генів, S (preSl, preS2) регіоні и) кодує головний, середній та великий білки (HBsAg). С і preC регіони кодують HBcAg і HBeAg, X регіон кед у є поліпептид, який експресується за час HBV інфекції Р регіон кодує білок з різноманітними функціями у реплікації. Ідентифіковано чотири класи HBV мРНК. У геномі HBV pre-S1 промотор продукує великий білок, pre-S2/S виробляє головний і середній білки. X промотор кодує 0,7 і 0,9 трагскрипти. С і пре-С промотори кодують Core і pol(HBVcAg) і HBeAg білки. Ключовими регуляторними елементами HBV є енхансери І і II. Активність енхансера II є специфічною для печінки. Він активує транскрипцію обох пре-S1 і пре-S2/S промоторів. Два HBV енхансери активують основні промотори HBV. Бокс-α в І 1-А і бокс-β в ІІ-В елементах у геномі HBV необхідні для функції енхансера II. Бокси а і р можуть регулювати активацію промотора Core, білки a, b, f і білки с, d прикріплюються у боксах а і р відповідно і впливають на енхансерну функцію. Геном вируса гепатита В человека (HBV) существует в виде двухцепочных кольцевых молекуул ДНК Он содержит четыре фланкирующие открытые рамки считывания (ORF8) генов. S (преS1, преS2) регион/ы) кодирует главный, средний и большой белки (HBsAg). С и пре-С регионы кодируют HBсAg и HBeAg. X регион кодирует полипептид, экспрессирующийся в течение HBV инфекции. Р регион кодирует белок с разнообразными функциями в репликации. Идентифицированы четыре класса HBV мРНК. В геноме HBV npe-Sl промотор продуцирует большой белок, пpe-S2/S промотор производит оба (главный и средний) белка. X промотор кодирует 0,7 и 0,9 транскрипты. С и пре-С промоторы кодируют Core и pol(HBcAg) и HBeAg белки. Ключевыми регуляторными элементами в HBV являются энхансеры I и II. Активность энхансера II очень специфична для печени, Энхансер II активирует транскрипционную активность пре-S1 и пре-S2/S про моторов. Два HBV энхансера активируют основные промоторы HBV. Вокс-α в НА и бокс-β в П-В элементах в геноме HBV необходимы для функции энхансера II. Воксы α и β могут регулировать активацию Core промотора, белки a, b, f и белки с, d прикрепляются в боксах α и β соответственно и действуют на энхансерную функцию.